Preparation and application of copper-sulfur group nano hydrogel
Through a multimodal tumor killing method based on copper chalcogen nanocomposites, combined with photothermal and chemodynamic therapy, the limitations of the traditional treatment plan for bladder cancer are solved, efficient tumor killing and long-term immune memory are achieved, and drug side effects and tumor recurrence risks are reduced.
Patent Information
- Application Number
- CN202411355354.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The traditional treatment plans for bladder cancer have problems such as short drug retention time, large local response, high tumor resistance and poor treatment effect, and the bladder's urine erosion and dilution mechanisms lead to a decrease in the effective treatment time and concentration of the drug.
A multimodal tumor killing method based on copper chalcogen nanocomposites is adopted, combined with photothermal therapy (PTT), chemodynamic therapy (CDT) and copper-induced cell death mechanisms, and the synergistic effect of chemotherapy and immunogenic cell death (ICD) is achieved through nanohydrogel-loaded bortezomib (BTZ).
It has achieved efficient killing of bladder cancer tumor cells, enhanced anti-cancer effects, stimulated the immune system's long-term defense ability against tumors, extended the retention time of drugs in the bladder, and reduced the side effects of drugs and the risk of tumor recurrence.
Smart Images

Figure CN119523882A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pharmaceutical preparations, and specifically relates to an anti-tumor nano preparation, a preparation method and use thereof. Background Art
[0002] In recent years, with the continuous development of nanotechnology, more and more technical systems have emerged. Figure 1-2 As shown, nanomaterials can carry various nanoscale particles and drugs. Through the researchers' precise design and surface modification, nanodrugs can maintain better specificity and bioavailability while reducing toxicity to healthy tissues, effectively overcoming the limitations of traditional chemotherapy regimens, not only improving the treatment effect, but also bringing a higher quality of life to patients.
[0003] Compared with other tumor types, the pathogenesis of bladder cancer has a unique physiological structure and characteristics. The bladder is a hollow structure organ located in the lower part of the abdominal cavity. Its main function is to store and discharge urine, and the smooth muscle structure of the bladder provides a large capacity. This closed cavity can accommodate various therapeutic drugs. The therapeutic drugs enter the bladder through the urethra, directly contact or even cover the bladder tumor, which can increase the local concentration of therapeutic drugs and avoid drug dilution caused by medication from the circulatory system. In addition, local administration can reduce the side effects of drugs, improve patient tolerance and the safety of treatment, thereby achieving precise treatment of bladder cancer. Therefore, the unique spatial structure of the bladder provides great convenience for nano-drug delivery to treat bladder cancer. However, due to the urination mechanism of the bladder, urine constantly flushes and dilutes the therapeutic drugs, resulting in a decrease in the effective treatment time and concentration of the drugs. Moreover, the interior of the bladder wall is lined with urothelium, whose tight connections make it difficult for conventional drug molecules to penetrate the bladder wall and penetrate into the tumor tissue. This stratified epithelium has a unique layer of flat "umbrella cells" that increase the surface area when stretched. In addition, the tight glycosaminoglycan barrier forms a mucin hydrophilic layer outside the urothelium, which has a strong resistance to the passage of molecules and becomes an important obstacle to the successful delivery of drugs in the bladder. At the same time, the traditional perfusion treatment of bladder cancer has many limitations, such as short drug retention time, large local drug reaction, high tumor resistance and poor drug treatment effect. Therefore, finding a treatment with superior therapeutic effect, low drug toxicity and side effects, high bioavailability and long-lasting action time is the focus of current bladder cancer treatment. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present application provides a copper-sulfide nanocomposite material, which combines photothermal therapy (PTT), chemodynamic therapy (CDT) and copper-induced cell death mechanism to achieve efficient killing of bladder cancer tumor cells. It can also induce immunogenic cell death (ICD), thereby enhancing the anti-cancer effect and stimulating the long-term defense ability of the immune system against tumors.
[0005] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A tumor-targeting nanocomposite material having the following structural formula: Cu 2-x Se@PDA@BTZ, the composite nanomaterial has a core-shell structure, including a core and a shell layer coated on the surface of the core, the core is Cu 2-x Se nanoparticles, the shell is coated with Cu 2-x A polydopamine (PDA) coating layer outside the Se nanoparticles, and a bortezomib (BTZ) material uniformly loaded on the surface of the PDA coating layer through chemical bonds.
[0007] Preferred Cu 2-x Se@PDA@BTZ nanocomposites also contain four-arm-polyethylene glycol-thiol (4ARM-PEG-SH), 4ARM-PEG-SH and Cu 2-x Se@PDA@BTZ nanocomposite cross-links to form nanohydrogels. The nanohydrogels are made of Cu 2-x Se@PDA@BTZ-Gel indicates.
[0008] On the other hand, the present invention also provides a method for preparing a tumor-targeting nanocomposite nanomaterial, the specific steps of which are:
[0009] S1: First, prepare Cu 2-x Se nanoparticles;
[0010] S2: The synthesized Cu 2-x One-pot synthesis of Cu by Se, dopamine hydrochloride and BTZ 2-x Se@PDA@BTZ.
[0011] Cu 2-x Se@PDA@BTZ-Gel is carried out in the following steps:
[0012] Weigh a certain amount of four-arm-polyethylene glycol-thiol (4ARM-PEG-SH) and dissolve it in deionized water. 2-x Se@PDA@BTZ mixed with four-arm-polyethylene glycol-thiol (4ARM-PEG-SH) solution can quickly form colloid at room temperature, that is, Cu 2- x Se@PDA@BTZ-Gel.
[0013] Preferably, S1 prepares Cu 2-x Se nanoparticles include the following steps:
[0014] (a) adding a certain amount of poly(4-styrene sulfonic acid) solution into pure water and stirring to obtain a mixed solution A;
[0015] (b) A certain amount of SeO2 is weighed and dissolved in deionized water to obtain a mixed solution B, a certain amount of Vc is weighed and dissolved in deionized water to obtain a mixed solution C, and a certain amount of CuSO4·5H2O is weighed and dissolved in deionized water to obtain a mixed solution D.
[0016] (c) adding solution A and solution C to the reaction container in sequence, stirring until the mixed solution completely turns orange-red, and then adding a certain amount of the mixed solution of B and C to the orange-red solution, stirring for a period of time, until it completely turns orange-red;
[0017] (d) After stirring at room temperature for a period of time, the solution color turned into emerald green, and then centrifuged and washed to obtain Cu 2-x Se nanoparticles.
[0018] One-pot synthesis of Cu in S2 2-x Se@PDA@BTZ includes the following steps:
[0019] (a) Prepare a Tris-HCl solution, weigh a certain amount of Tris and dissolve it in deionized water, use it after calibrating the pH detector, and adjust the pH value of the Tris-HCl solution to 8-10 with an acid solution;
[0020] (b) Prepare a reaction vessel with a rotor and add a certain amount of Cu 2-x Se solution; then add a certain amount of Tris-HCl solution;
[0021] (c) weighing a certain amount of dopamine hydrochloride and dissolving it in a Tris-HCl solution, and adding a certain volume of the dopamine hydrochloride solution into a reaction container;
[0022] (d) Weigh a certain amount of BTZ and dissolve it in DMSO to obtain a mixed solution containing BTZ, and add the mixed solution to a reaction container, place it on a stirrer and stir for 6-8 hours until the color of the solution turns dark green, then centrifuge, filter, wash, and dry to obtain Cu 2-x Se@PDA@BTZ composite materials.
[0023] Preferably, the stirring time in step c of step S1 is 5-30 min; the stirring time in step D is 15-24 h;
[0024] In the preferred step S2, the pH value in step a is 8.5;
[0025] Preferably, the acid in step a of step S2 can be one or more of phosphoric acid, sulfuric acid, nitric acid, acetic acid, formic acid, and hydrochloric acid, and more preferably hydrochloric acid.
[0026] Preferably, the centrifugal conditions of step d in step S1 are: speed 10000-14000 rpm / min, time 10-15 min.
[0027] Preferably, the centrifugal conditions of step d in step S2 are: speed 10000-14000 rpm / min, time 10-15 min.
[0028] The above tumor-targeted nanocomposite material or the nanocomposite material prepared by the above method is used in preparing anti-tumor drugs; the tumor is bladder cancer.
[0029] The beneficial effects of the present invention are:
[0030] (1) In this study, PDA was used to 2-x Se surface modification, Cu 2-x Se is wrapped inside PDA, and bortezomib (BTZ) can be connected to PDA through a phenylboronic acid ester bond. The outermost layer PDA of the nanocomposite material of the present invention can be cross-linked with four-arm-polyethylene glycol-thiol (4ARM-PEG-SH) to form a nanohydrogel, which can make the sulfide nanocomposite hydrogel extend the retention time of the drug in the bladder, enhance the contact time between the bladder mucosa and the drug, exert the sustained release effect of the drug, and realize the efficient use of the drug;
[0031] (2) Multimodal tumor killing: By utilizing the photothermal effect (PTT), chemokinetic effect (CDT) and copper-induced cell death mechanism of copper sulfide nanohydrogels, a multifunctional tumor killing method is provided to overcome the problem of insufficient efficacy of single treatment methods;
[0032] (3) Synergistic effect of chemotherapy drugs: Bortezomib (BTZ) loaded on nanohydrogels not only exerts its chemotherapy effect, but also further enhances its anti-cancer effect by inducing immunogenic cell death (ICD), thus solving the problem of insufficient ability of traditional chemotherapy drugs to stimulate the immune system.
[0033] (4) Copper sulfide nanohydrogels have high biocompatibility and biosafety. Their good bioavailability ensures the high efficacy of drugs in the bladder, solving the problems of drug side effects and biosafety in traditional bladder cancer treatment. At the same time, the long-term immune memory ability induced by nanohydrogels effectively reduces the risk of bladder cancer recurrence, solving the clinical problem of high recurrence rate of bladder cancer. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1These are the transmission electron microscope images of CS of the present invention, the transmission electron microscope image of CSP, the transmission electron microscope image of CSBP, and the EDS detection image of CSBP.
[0035] Figure 2 This is the SEM image of CSBP-Gel of the present invention.
[0036] Figure 3 The ultraviolet absorption spectra of CSBP of the present invention at different concentrations.
[0037] Figure 4 Storage modulus (G') and loss modulus changes (G") during the gelation process of nanohydrogel.
[0038] Figure 5 This is the uptake behavior of the nanomaterials by MB49 cells of the present invention.
[0039] Figure 6 The long-term retention effect and permeation effect of nanohydrogel. DETAILED DESCRIPTION
[0040] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0041] In the present invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple.
[0042] The invention and its beneficial effects are described in further detail, but the embodiments of the invention are not limited thereto.
[0043] The present invention prepares Cu by one-pot method from Vc, SeO2 and CuSO4 2-x Se, the successfully prepared Cu 2-x Se nanoparticles were encapsulated in polydopamine (PDA) and loaded with the small molecule chemotherapy drug bortezomib (BTZ) on its surface. Subsequently, a hydrogel system was formed by reacting with four-arm polyethylene glycol thiol (4-ARM-PEG-SH). Based on the sustained release properties of the hydrogel, we were able to achieve the synergistic effect of the nanosystem in the bladder cavity and release Cu 2-xSe@PDA@BTZ nanoparticles are slowly released into bladder cancer cells. Due to the weak acidity, high glutathione (GSH) and high hydrogen peroxide (H2O2) levels of the tumor microenvironment, Cu 2-x2- x The release of Se and BTZ enhances the targeting ability of nanoparticles. 2-x Se reacts with GSH in the tumor to generate monovalent copper ions, inducing copper death (cuproptosis); on the other hand, the released BTZ kills the tumor synergistically through chemotherapy and immunogenic cell death (ICD) effects. Through the combined action of multiple mechanisms, effective treatment of bladder cancer is achieved. In addition, our study also found that Cu 2-x Se exhibits localized surface plasmon resonance (LSPR) characteristics in the near-infrared region and has a high photothermal conversion efficiency. Irradiation with 1064nm laser can induce a photothermal effect, further inhibit tumor cell proliferation, and synergize with copper death and ICD effects, thereby effectively improving the therapeutic effect.
[0044] This application is also based on the multifunctional properties of copper sulfide nanohydrogels. This effectively kills tumor cells through photothermal therapy (PTT), chemodynamic therapy (CDT) and copper-induced cell death mechanisms. At the same time, the nanohydrogel can be loaded with the chemotherapy drug bortezomib (BTZ), which not only has a chemotherapeutic effect, but also can induce immunogenic cell death (ICD), further enhancing the anti-cancer effect. Copper sulfide nanohydrogels have high biocompatibility and safety, and their high bioavailability improves the therapeutic effect of bladder cancer. In addition, nanohydrogels can also induce long-term immune memory and reduce the risk of bladder cancer recurrence.
[0045] In the following examples, unless otherwise specified, the raw materials and instruments used are commercially available.
[0046] Example 1
[0047] First, Cu 2-x Se nanoparticles.
[0048] (1) Add 0.16 g of poly(4-styrene sulfonic acid) solution to 16 ml of pure water and add it to a round-bottom flask. Then add 55 ml of deionized water to the round-bottom flask and place a magnetic stirrer at the bottom of the flask.
[0049] (2) Weigh 22.192 mg of SeO2 and dissolve it in 1 ml of deionized water (0.2 M), weigh 211.344 mg of Vc and dissolve it in 3 ml of deionized water (0.4 M), weigh 99.876 mg of CuSO4·5H2O and dissolve it in 1 ml of deionized water (0.4 M), and weigh 282 mg of Vc and dissolve it in 4.7 ml of deionized water (0.4 M). The dissolution process can be accelerated using an ultrasonic device.
[0050] (3) SeO2 and 3 ml of Vc were added to the round-bottom flask in sequence and stirred for 10 minutes. When the solution completely turned orange-red, a mixed solution of CuSO4·5H2O and 4.7 ml of Vc was added and the solution turned brown.
[0051] (4) After stirring at room temperature for 17 hours, the solution turned emerald green and was transferred to a small tube. Centrifuged at 14.8Krpm for 10 minutes, the supernatant was removed, and the precipitate was collected. The precipitate was washed with pure water, centrifuged repeatedly, and the supernatant was removed. Finally, it was dissolved in 5 ml of pure water. 2-x Se(CS) was successfully prepared. The prepared nanomaterials were placed in a 4-degree refrigerator.
[0052] Example 2
[0053] We will synthesize the Cu 2-x One-pot synthesis of Cu from Se, dopamine hydrochloride and BTZ 2-x Se@PDA@BTZ, the specific steps are as follows:
[0054] (1) Prepare Tris-HCl solution. Weigh 0.363 g Tris and dissolve it in 300 ml deionized water. Calibrate the pH meter before use. Adjust the pH value of the Tris-HCl solution to 8.5 with HCl solution.
[0055] (2) Prepare a small bottle with a rotor and add 0.5 ml of Cu 2-x Se solution. Then add 8.5 ml of Tris-HCl solution.
[0056] (3) Weigh 6 mg of dopamine hydrochloride and dissolve it in 1 ml of Tris-HCl solution. Add 0.5 ml of dopamine hydrochloride solution into the bottle.
[0057] (4) Weigh 2 mg BTZ and dissolve it in 800 μl DMSO, then add it to the bottle. (If this step is not performed, the final solution will be Cu 2-x Se@PDA)
[0058] (5) Place the vial on a magnetic stirrer and stir for 6 h until the solution turns dark green.
[0059] (6) The solution was transferred to a small tube, centrifuged at 14.8 thousand rpm for 10 minutes, the supernatant was removed, the precipitate was retained, washed with pure water, and centrifuged as above, the supernatant was removed, and finally dissolved in 1 ml of pure water. The prepared nanomaterials were placed in a refrigerator at 4 degrees.
[0060] Example 3
[0061] Cu 2-x Preparation of Se@PDA@BTZ-Gel:
[0062] Weigh 100 mg of 4ARM-PEG-Thiol and dissolve it in 1 ml of deionized water. 2-x Se@PDA@BTZ was concentrated to 150 μl and mixed with 4ARM-PEG-Thiol solution at a ratio of 1:1, which quickly formed a colloid at room temperature.
[0063] Example 4
[0064] Cu 2-x Se@PDA@BTZ and Cu 2-x Verification of cell uptake of Se@PDA:
[0065] (1) Sterilize the sterile operating table. Prepare DMEM culture medium, DMSO, sterile PBS, FBS, double antibodies (penicillin and streptomycin), sterile centrifuge tubes, and confocal culture dishes.
[0066] (2) Pre-treat the confocal culture dish. Add 3 ml of culture medium into the confocal culture dish and place it in the incubator for 15 minutes before taking it out for use.
[0067] (3) Take out the culture dish containing MB49 cells and observe the morphology and health of the cells. Wash with sterile PBS, digest with trypsin, terminate digestion, centrifuge, and suspend the cells (operation is the same as before).
[0068] (4) Remove the culture medium from the confocal dish and add 500 μM complete culture medium with MB49, with a cell count of about 8*10^4. Incubate in the incubator for 2 hours and wait for the cells to adhere.
[0069] (5) Take out the confocal culture dish, add complete medium to 2 ml, and incubate in an incubator overnight.
[0070] (6) Preparation of nanomaterials connected to CY5.5, 10 μl Cy5.5-NHS (10 mg.ml-1), 1 ml Cu 2-x Se@PDA@BTZ or Cu 2-xSe@PDA solution (concentration), EDC aqueous solution (100mg / ml), mix the three solutions and incubate overnight in the dark. The next day, centrifuge at 14.8k rpm, remove the supernatant, wash twice with deionized water, and use a UV spectrophotometer to detect the absence of Cy5.5 absorption peak in the supernatant. Finally, the nanomaterial is fixed to 1ml.
[0071] (7) Observe the morphology and health of the cells in the confocal culture dish. If the cells are in good condition, remove the supernatant, add pure DMEM culture medium, add 20 μg of Cy5.5-loaded nanomaterials (calculated based on copper content), and add 2 ml of culture medium, and incubate in the incubator for 4 hours. Lysosomal green fluorescent probe (Lyso-Tracker Green) dye is added to the culture medium at a dilution of 1:20,000 to a final concentration of 50 nM, and incubate in the incubator for 1 hour.
[0072] (8) After incubation, the confocal dish was washed three times with PBS, each time for 5 min, to remove the nanoparticles and lysosomal dyes that did not enter the cells.
[0073] (9) Fix the cells with 4% PFA and let stand for 20 min.
[0074] (10) Prepare DAPI storage solution by diluting 0.5 mg of DAPI dye with 5 ml of saline. Dilute the working solution 1000 times with saline before use.
[0075] (11) After fixation, wash with PBS three times, 5 min each time, add 200 μl DAPI working solution, and stain for 10 min in the dark.
[0076] (12) After staining, wash three times with PBS, 5 min each time, to remove free dye and then put it on the machine.
[0077] Example 5
[0078] Cu 2-x Se@PDA@BTZ and Cu 2-x Retention experiment of Se@PDA@BTZ-Gel:
[0079] (1) Cu 2-x Se@PDA@BTZ labeled Cy5.5 using the same method as before.
[0080] Cu 2-x Se@PDA@BTZ-Gel is composed of Cu 2-x Se@PDA@BTZ was labeled with Cy5.5 and then formed into a gel with 4arm-PEG-Thiol.
[0081] (2) Use normal saline to prepare the anesthetic, and the concentration of sodium pentobarbital is 1%.
[0082] (3) Mice aged 6-8 weeks, weighing between 20-30 g, were selected and divided into two groups. One group was used for perfusion of Cu 2-x Se@PDA@BTZ-Gel, another group for Cu 2-x Se@PDA@BTZ.
[0083] (4) Prepare the following equipment: syringe, alcohol cotton, tweezers, microhemostatic clamps, animal shaver, disposable intravenous catheter (for infusion) and weighing scale.
[0084] (5) Catch the mouse, weigh it, disinfect its abdomen with alcohol cotton, insert the needle obliquely downward into the mouse's lower abdomen, and inject anesthetic at a rate of 7.5 mg / kg.
[0085] (6) The nanocomplex was sucked up with a 29 g fine needle and inserted into a disposable intravenous catheter. The mouse urethra was clamped with forceps and the intravenous catheter was slowly inserted into the bladder. An equal amount of nanocomplex was injected. The urethra was clamped with a hemostatic clip and the intravenous catheter was slowly removed. The hemostatic clip was removed after 1.5 h.
[0086] (7) Use a shaver to shave the hair on the mouse's abdomen. Use a two-color infrared laser imaging system to image the mouse. The fluorescent signal of the material labeled with Cy5.5 is red. Image the mouse at 2h, 6h, 24h, 48h, and 72h.
[0087] Preparation and testing of electron microscopy samples:
[0088] Take out the membrane from the carbon support film and place it on the filter paper. Carefully drop 2μl of the nanomaterial on the membrane surface. After air drying, take a sample for TEM and SEM electron microscopy. For the sample preparation of nanohydrogel, freeze the nanohydrogel at -80 for 2h, then place it in a freeze dryer. After freeze drying for 24h, the sample preparation is complete and the morphology can be photographed with an electron microscope.
[0089] Cu 2-x Rheological properties of Se@PDA@BTZ-Gel:
[0090] The rheological properties of the hydrogel were tested using a rheological instrument. 2-x The concentrated solution of Se@PDA@BTZ and four-arm mercapto polyethylene glycol were placed on the rheometer test platform for dynamic viscosity test and modulus test (storage modulus and loss modulus). The temperature condition was 37°, the angular velocity was set to 10 rad / s, and the stress was set to 0.1%.
[0091] We will Cu 2-x Se nanoparticles are abbreviated as CS, Cu 2-x Se@PDA nanoparticles are abbreviated as CSP, Cu 2-x Se@PDA@BTZ nanoparticles are abbreviated as CSBP, Cu 2-x Se@PDA@BTZ-Gel is abbreviated as CSBP-Gel.
[0092] Figure 1 (a) TEM image of CS, scale bar: 50 nm; (b) TEM image of CSP, scale bar: 50 nm; (c) TEM image of CSBP, scale bar: 50 nm; (d) EDS detection of elemental mapping of Cu, Se, C, N, B and O in CSBP. The morphology of CS in TEM is spherical, and polydopamine is modified and wrapped on the surface of CS to form CSP. The contrast of PDA is lower than that of Cu. 2-x Se, the dispersion is relatively uniform. Since BTZ is a small molecule, the morphology of CSP and CSBP is similar. From the electron microscope image, the size of the nanoparticles ranges from 50 to 100 nm. The EDS image can be used to observe the element distribution (2-1d). In the figure, we can see that Cu, Se, N, C, O, and B are evenly distributed on each nanoparticle. Although the B element is less, its morphology can still be observed, indicating that PDA successfully transfers Cu 2-x Se wrapped and successfully loaded BTZ.
[0093] Figure 2 This is the SEM image of CSBP-Gel. We can see that the results show that at a field of view of 200 μm, the nano-hydrogel is a lamellar structure. Figure 2-6 (b) The result is a 200nm field of view. It can be observed that the nanomaterial has a 3D spherical structure with a diameter less than 100nm. This is because the Cu 2-x Se is stacked.
[0094] Figure 3 This is the UV absorption spectrum of CSBP at different concentrations. It can be seen that the UV absorption peak of the nanomaterial increases from low concentration to high concentration, and the entire curve is smooth without obvious broken lines or scattered graphs, indicating that the concentration of the nanomaterial we measured is within the limit, proving the reliability of the data.
[0095] Figure 4It is the change of storage modulus (G') and loss modulus (G") during the gelation process of nanohydrogel; as well as the shear thinning ability of nanohydrogel. It can be observed that when the nanomaterial is mixed with 4arm-PEG-Thiol, a gel state can appear in a very short time. The storage modulus is greater than the loss modulus, which means it is in a gelation state. The storage modulus increases rapidly within 500s, indicating that the gelation time of the nanohydrogel we prepared is very short. The two can be transformed from liquid to gel within a few seconds after mixing. In addition, we tested the shear thinning properties of the nanomaterial. The viscosity is on the y-axis and the shear rate is on the x-axis. As the shear thinning rate increases, the viscosity continues to decrease, indicating that the hydrogel has the ability of shear thinning, and also shows that the nanohydrogel can be injected through a syringe.
[0096] Figure 5 CSP-Cy5.5 and CSBP-Cy5.5 were incubated with MB49 for 4 hours, and the confocal images of lysosomes were incubated for 1 hour. The nucleus was stained with DAPI (blue), the lysosomes were stained with Lyso-Tracker Green (green), and the cytoplasm was stained after the nanomaterials entered the cell (red). The uptake of CSBP and CSP by MB49 cells was measured by confocal laser microscopy, and the distribution of nanomaterials after entering the cells was evaluated by fluorescently labeled lysosomes. The confocal images showed that both CSP and CSBP had strong Cy-5.5 signals. From the co-localization images of lysosomes and staining and nanomaterials, it can be observed that lysosomes can assist in the transport of nanomaterials and enhance the cellular delivery ability of nanomaterials. In short, nanomaterials can be efficiently taken up by MB49 mouse bladder cancer cells.
[0097] Figure 6(a) Cryosection of mouse bladder, DAPI staining of cell nuclei (blue), Cy5.5 localization of CSBP-Gel and CSBP (red), scale bar: 25 μm, nanomaterials and nanohydrogels containing equal amounts of CSBP were instilled into the mouse bladder, and images were taken at 2 h, 6 h, 24 h, 48 h, and 72 h, respectively. CSBP was almost completely emptied within 2 h, while the red fluorescence signal of Cy5.5 could still be detected in CSBP-Gel until 72 h, proving the long retention effect of the nanohydrogel. In addition, the mice did not show symptoms such as difficulty in urination, physical weakness, and weight loss during the whole process, indicating that CSBP-Gel has good biocompatibility. Subsequently, we dissected the mice at the end of the observation and prepared mouse bladder tissue samples by frozen sections. After nuclear staining, we could observe that there were still hydrogels remaining in the bladder wall of the mice in the CSBP-Gel group. Some hydrogels had disintegrated, and the Cy5.5-loaded nanoparticles had entered the cytoplasm, indicating that the hydrogels could not only remain in the bladder continuously, but also further deliver CSBP to the bladder cells.
[0098] Through the above experiments, it can be seen that the PDA of this application is successfully applied on Cu 2-x Se surface modification, BTZ is a small molecule chemotherapy drug that is poorly soluble in water. We dissolved it in DMSO and connected it to DA through a boronate bond to stably load it on CSBP, which not only solved the toxic side effects of chemotherapy drugs, but also achieved targeted drug delivery. EDS proved that the nanocomposite material is composed of Cu, Se, N, C, O and B. The excellent photothermal conversion ability of CSBP and CSBP-Gel demonstrates the diversity of nanomaterial functions. CSBP-Gel has the ability of rapid gelation and shear thinning. By instilling CSBP-Gel in the bladder, due to the special structure and surface properties of the hydrogel, it can be attached to the bladder wall for a long time, verifying the excellent long-term retention ability and biocompatibility of the hydrogel. When the nanomaterials enter the cells through the lysosomal pathway, the weak acid environment, high GSH and high H2O2 in the bladder cancer tumor microenvironment can react with CSBP and cause complete decomposition of CSBP, further enhancing the bioavailability of the chemotherapy drug BTZ and realizing the chemokinetic effect of copper ions. The synthesized CSBP nanohydrogel has good biocompatibility and biosafety. As a carrier for delivering nanodrugs and chemotherapy drugs, it can realize the synergistic treatment of multiple methods such as photothermal therapy, chemodynamic therapy, chemotherapy, etc., and has broad application prospects.
[0099] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A tumor-targeting nanocomposite material, the nanocomposite material having the following structural formula: Cu 2-x Se@PDA@BTZ, characterized by: The composite nanomaterial has a core-shell structure, including a core and a shell layer coated on the surface of the core, wherein the core is Cu 2-x Se nanoparticles, the shell is coated with Cu 2-x A polydopamine (PDA) coating layer on the surface of Se nanoparticles, and a bortezomib (BTZ) material uniformly loaded on the surface of the PDA coating layer through chemical bonds.
2. The nanocomposite material according to claim 1, characterized in that The Cu 2-x Se@PDA@BTZ nanocomposites also contain four-arm-polyethylene glycol-thiol (4ARM-PEG-SH), 4ARM-PEG-SH and Cu 2-x Se@PDA@BTZ nanocomposite cross-links to form nanohydrogels. The nanohydrogels are made of Cu 2-x Se@PDA@BTZ-Gel indicates.
3. A method for preparing a tumor-targeting nanocomposite nanomaterial as claimed in claim 1 or 2, characterized in that: Cu 2-x Se@PDA@BTZ proceeds as follows: S1: First, prepare Cu 2-x Se nanoparticles; S2: The synthesized Cu 2-x One-pot synthesis of Cu by Se, dopamine hydrochloride and BTZ 2-x Se@PDA@BTZ. Cu 2-x Se@PDA@BTZ-Gel is carried out in the following steps: Weigh a certain amount of four-arm-polyethylene glycol-thiol (4ARM-PEG-SH) and dissolve it in deionized water. 2-x Se@PDA@BTZ was mixed with four-arm-polyethylene glycol-thiol solution (4ARM-PEG-SH) and quickly formed colloid at room temperature, i.e., Cu 2-x Se@PDA@BTZ-Gel.
4. The preparation method according to claim 3, characterized in that: Prepared Cu 2-x Se nanoparticles include the following steps: (a) adding a certain amount of poly(4-styrene sulfonic acid) solution into pure water and stirring to obtain a mixed solution A; (b) A certain amount of SeO2 is weighed and dissolved in deionized water to obtain a mixed solution B, a certain amount of Vc is weighed and dissolved in deionized water to obtain a mixed solution C, and a certain amount of CuSO4·5H2O is weighed and dissolved in deionized water to obtain a mixed solution D. (c) adding solution A and solution C to the reaction container in sequence, stirring until the mixed solution completely turns orange-red, and then adding a certain amount of the mixed solution of B and C to the orange-red solution, stirring for a period of time, until it completely turns orange-red; (d) After stirring at room temperature for a period of time, the solution color turned into emerald green, and then centrifuged and washed to obtain Cu 2-x Se nanoparticles.
5. The preparation method according to claim 3, characterized in that: One-pot synthesis of Cu 2-x Se@PDA@BTZ includes the following steps: (a) Prepare a Tris-HCl solution, weigh a certain amount of Tris and dissolve it in deionized water, use it after calibrating the pH detector, and adjust the pH value of the Tris-HCl solution to 8-10 with an acid solution; (b) Prepare a reaction vessel with a rotor and add a certain amount of Cu 2-x Se solution; then add a certain amount of Tris-HCl solution; (c) weighing a certain amount of dopamine hydrochloride and dissolving it in a Tris-HCl solution, and adding a certain volume of the dopamine hydrochloride solution into a reaction container; (d) Weigh a certain amount of BTZ and dissolve it in DMSO to obtain a mixed solution containing BTZ, and add the mixed solution to a reaction container, place it on a stirrer and stir for 6-8 hours until the color of the solution turns dark green, then centrifuge, filter, and wash to obtain Cu 2-x Se@PDA@BTZ composite materials.
6. The preparation method according to claim 4, characterized in that: The stirring time in step C is 5-30 min; the stirring time in step D is 15-24 h.
7. The preparation method according to claim 5, characterized in that: The pH value in step a is 8.
5.
8. The preparation method according to claim 5, characterized in that: The acid in step a can be one or more of phosphoric acid, sulfuric acid, nitric acid, acetic acid, formic acid, and hydrochloric acid, preferably hydrochloric acid.
9. The preparation method according to any one of claims 3 to 4, characterized in that: The centrifugal conditions are: speed 10000-14000 rpm / min, time 10-15 min.
10. Use of the nanocomposite material according to claim 1 or 2 or the nanocomposite material prepared by the method according to claim 2 to 9 in the preparation of anti-tumor drugs; the tumor is bladder cancer.
Citation Information
Patent Citations
Nanometer drug-loading system as well as preparation method and application thereof
CN105030795A
Preparation method and application of drug-loaded copper sulfide polyethylene glycol hydrogel composite polycaprolactone scaffold
CN117159806A
Cited By
Antibody conjugate as well as application and pharmaceutical composition thereof
CN121081665A